Diagnosis and treatment of otomycosis in southern China. Issue 11 (2nd September 2019) - Li, Yongqi; He, Lifeng
Summary: To analyse and discuss the clinical features and pathogenic characteristics, diagnosis and treatment of patients with otomycosis in southern China. Two hundred fifty‐six patients from southern China diagnosed with otomycosis were randomly separated into two groups: the drug filling group and drug smearing group. Patients in the drug filling group were first examined and then had the pathogenic secretions in their external auditory canals cleared by otoendoscopy. Then, the local antifungal cream triamcinolone acetonide clotrimazole was injected into the external auditory canal. The same treatment was undertaken 1 week later and repeated once or twice more. Patients in the drug smearing group were also treated by otoendoscopy. Then, they were told to smear their external auditory canals once per day with the antifungal cream. All cases were followed for more than 6 months after the 3‐ to 4‐week treatment. The main symptoms and otoendoscopic examination were used to evaluate the prognosis. Aspergillus was the commonest fungus. The cure rate was 93% in the drug filling group and 81% in the drug smearing group. Otomycosis is very common in southern China, but it lacks characteristic features in its early stages. Once diagnosed, the local lesions in the external auditory canal should be cleared thoroughly using otoendoscopy, and then, the local antifungal cream is injected into external auditory canal. The cure rate can be significantly improved with the foregoing treatment.